Translating Irony in Popular Fiction: Dashiell Hammett’s The Maltese Falcon - Linder, Daniel (Linguistica Antverpiensia, New Series – Themes in Translation Studies, 2021)
In Dashiell Hammett ’s The Maltese Falcon (1929), detective Sam Spade uses obscure language to threaten Wilmer Cook, a young homosexual employed by crimeboss Caspar Gutman. What Spade says to Gutman,— “That daughter of yours has a nice belly (...) too nice to be scratched up with pins"— refers literally to how his daughter, while drugged, scratched herself on the stomach with a bouquet-pin to keep awake. However, the statement contains an ironically encoded message for Wilmer: “It would be too bad if I had to shoot (scratch up with pins) your young homosexual lover (daughter of yours).” This sentence carries both the literal and ironic meaning at the same time. In this paper, I will examine how the Spanish translations (1933, Casas Gancedo; 1946, Warschaver; 1958, Calleja; and 1992, Páez de la Cadena) dealt with the dually encoded meaning of the sentence. Because the same-sex love relationship was hidden behind specialized slang and because Spade ’s sentence is so cleverly worded, the translators have overlooked the ironic meaning entirely.